2011
DOI: 10.1021/ar200037t
|View full text |Cite
|
Sign up to set email alerts
|

Biomedical Applications of Tetrazine Cycloadditions

Abstract: Conspectus Disease mechanisms are increasingly being resolved at the molecular level. Biomedical success at this scale creates synthetic opportunities for combining specifically designed orthogonal reactions in applications such as imaging, diagnostics, and therapy. For practical reasons, it would be helpful if bioorthogonal coupling reactions proceeded with extremely rapid kinetics (k > 103 M−1 sec−1) and high specificity. Improving kinetics would minimize both the time and amount of labeling agent require… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
374
0
4

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 450 publications
(387 citation statements)
references
References 55 publications
5
374
0
4
Order By: Relevance
“…Inspired by the work of Dommerholt et al 96 , it was found that trans-bicyclononene reacted at yet faster rates (while noting the caveats on rate determinations given above) 103 . In addition to allowing labelling of highly dynamic processes, such rapid and efficient reactions allow the concentrations of reactive partners to be lowered significantly, reducing background labelling particularly in cases where it is REVIEW implausible to wash away excess reagent, such as intracellularly or in animal models 104 .…”
Section: Review Nature Communications | Doi: 101038/ncomms5740mentioning
confidence: 99%
“…Inspired by the work of Dommerholt et al 96 , it was found that trans-bicyclononene reacted at yet faster rates (while noting the caveats on rate determinations given above) 103 . In addition to allowing labelling of highly dynamic processes, such rapid and efficient reactions allow the concentrations of reactive partners to be lowered significantly, reducing background labelling particularly in cases where it is REVIEW implausible to wash away excess reagent, such as intracellularly or in animal models 104 .…”
Section: Review Nature Communications | Doi: 101038/ncomms5740mentioning
confidence: 99%
“…The formed ''click'' products may be characterised, in addition to these techniques, with more sophisticated methods, such as MALDI-TOF-MS (matrixassisted laser desorption ionisation time-of-flight mass spectrometry) 20,24 or SEC (size exclusion chromatography). 12 Therefore, this section concentrates on the underlying chemistry to give an impression that features of iEDDA are responsible for its success in life sciences and could also be of interest for other fields. Herein, we focus on the three most impressive features of iEDDA: fast reaction rates, bioorthogonality and mutual orthogonality with other click reactions.…”
Section: Iedda Precursorsmentioning
confidence: 99%
“…Also,t he amino-propyl groups on the surface of MSNs were partially modified with PEG-linker-RGD peptide by the bioorthogonal tetrazine-TCO ligation reaction and copper-free DBCOazide click chemistry. [13] RGD peptide and PEG linker were previously shown to improve the nanoparticles cellular uptake and prevent their intracellular aggregation. [14] Upon cellular uptake (Steps I, II in Scheme 1) and successful endosomal/lysosomal escape (Step III), the hybridization of the complementary sequences between Ant122 and intracellular miR-122 produced arigid double helical structure and altered the conformation of Ant122, which would reduce the binding capacity of Ant122 and lead to the uncapping of the MSNs.…”
Section: Angewandte Communicationsmentioning
confidence: 99%